Perspektif Hukum Islam Pasal 53 Tentang Pernikahan Wanita Hamil Di Luar Nikah Dan Korelasinya Dengan Hadits Riwayat Muslim - Teguh Abdurrohman Shodiq; Tajul Arifin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The marriage of women who are pregnant out of wedlock or due to adultery is a complex issue within the context of Islamic law itself. Article 53, in the view of Islamic law regarding such marriages, becomes a significant subject of debate in contemporary Islamic legal discussions. This article will present the perspective of Islamic law on the marriage of pregnant women out of wedlock, with an emphasis on Article 53 and its correlation with the Hadith narrated by Muslim. Marriage in Islam is governed by certain principles that emphasize the importance of justice, honor, and responsibility. Marriage is a legal bond between two individuals who mutually agree and commit to each other. However, pregnancy out of wedlock introduces its own complexities within the context of Islamic law. Article 53, in some interpretations, reflects views on how Islamic law treats such marriages. The correlation between Article 53 and the Hadith narrated by Muslim adds to the complexity of understanding Islamic law related to the marriage of pregnant women out of wedlock. The Hadith narrated by Muslim is one of the primary sources in Hadith literature that is often cited to show the views of Prophet Muhammad (PBUH) on various aspects of life, including marriage and family. An analysis of this Hadith helps interpret the Islamic view on marriage out of wedlock. This article aims to comprehensively analyze these two perspectives. The correlation between Article 53 and the Hadith narrated by Muslim will be explored to understand a comprehensive Islamic legal perspective on the marriage of pregnant women out of wedlock. The legal and moral implications of this perspective will be discussed, considering various interpretations and social contexts. A better understanding of Islamic law related to such marriages is essential for addressing contemporary issues related to morality, justice, and responsibility in Muslim societies.